Advantages and disadvantages of killed and live poliomyelitis vaccines - Melnick, Joseph L. (1978)
Decision-making on the use of poliomyelitis vaccines in the WHO Expanded Immunization Programme, and particularly in the developing nations, needs to be based on an understanding of the epidemiology of poliomyelitis in different parts of the globe. Even with two safe and effective kinds of poliomyelitis vaccine available, poliomyelitis has by no means been eradicated from the world. In developed countries that are considered well-vaccinated, certain sectors of the population may be inadequately protected against risk of infection by indigenous or imported wild polioviruses. In developing nations that are in transition toward an epidemic phase of poliomyelitis, wild polioviruses will continue to be a threat until thorough immunization is established and maintained. Killed-virus poliomyelitis vaccines have proved to be effective in certain countries that have used them exclusively; these are small countries with excellent public health systems, where coverage by the killed vaccine has been wide and frequent. Live vaccines, administered to hundreds of millions of persons during the past decade, have also been remarkably safe and effective. However, in certain warm-climate countries induction of antibodies in a satisfactorily high proportion of vaccinees has been difficult to accomplish. The advantages and disadvantages of each kind of poliomyelitis vaccine need to be weighed with respect to the particular setting in which a vaccine has been or will be used.